Customer experience management: Underexplored instrument for customer transformation - David Havíř (Trends Economics and Management, 2021)
Purpose of the article: The purpose of this article is to identify the role the customer experience plays in the transformation of the customer and to develop a theory that brings together related concepts in order to position the phenomenon of customer experience in the macromarketing context. Methodology/methods: The grounded theory development approach is based upon the sequential search and content analysis of the research papers acquired primarily from Scopus and Web of Science databases and by the process of citation chaining. Scientific aim: The aim of this article is to identify customer experience related concepts and relationships between them to lay the foundation for empirical research in the area of customer experience and transformation management. Findings: The research points out to the significant role of the customer experience in the transformation of the customer and therefore to the necessity to approach marketing initiatives to customer experience management thoroughly to achieve the desired marketing results, but also responsibly and ethically to promote growth not the degradation of the society. Conclusions: The cycle of the customer transformation as outlined through the conceptual model contains weak spots which can provide free space for negative effects of the company's outputs on the customer. The trend of digitisation and digital products can significantly amplify this possibility and increase the overall negative effect. From another standpoint, several problematic spots can cause difficulties for companies intentionally trying to transform the customer through their outputs, namely intent-result gap, reality-perception gap, single-part gap, and experience-memory gap. Scientific research in this area might support the effectiveness of marketing initiatives, increase transparency in the field of customer experience and transformation, and lead to increased customers' well-being, long-term happiness, life satisfaction, and quality of life.
Keywords: M31; D91; 650; customer experience; transformation economy; ethics; macromarketing; positive marketing